Strategi Inisiatif Zakat Indonesia (IZI) Dalam pemberdayaan Mustahik Melalui Program pelatihan Pangkas Rambut - Risky A’aliyah; Hilda; Rachmania (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
This research is entitled "Indonesian Zakat Initiative (IZI) Strategy in empowering Mustahik through barber training programs". This research aims to see whether the strategy in running the barber training program has an influence on the success of the program as well as competency and has an impact on improving the standard of living of the Mustahik beneficiaries of the training program. The research method used is a qualitative research method with data collection techniques through observation and interviews. The research location was carried out in Palembang and primary data was obtained through the final program report and interviews with 5 informants. One of the informants is a representative of the South Sumatra IZI Institute while the other is a beneficiary of the training program. The research results obtained through observation, data analysis and affirmation show that the strategy in running the barber training program has an influence on the success of the program and has an impact on the competency and standard of living of Mustahik.